THE EFFECT OF INDUCTION DURING GENERAL ANESTHESIA ON CHANGES IN HEMODYNAMICS AND RESPIRATION PATIENT AT THE CENTRAL SURGICAL INSTALLATION - Suanda Saputra; Siti Umaroh; Sahat T. Salomo (Journal of Indonesian Anesthesiology Nursing, 2024)
Induction in general anesthesia is the act of making a conscious patient unconscious which occurs in stage 1 or the analgesia stage. At the beginning of induction hemodynamics and respiration undergo significant changes. Objective: Knowing the effect of induction during general anesthesia on changes in hemodynamics and respiration of patients in the Central Surgical Installation (IBS) of Bayu Asih Hospital, Purwakarta Regency. Methods: The research method used is quantitative method with Cross Sectional approach. With sampling techniques using Accidental Sampling with a total of 36 respondents. The research instrument used an observation sheet. Data analysis technique with Simple Linear Regression analysis with P <0,050. Results: Probability value 0,667 > 0,050 means there is no effect of induction on hemodynamic changes, the second linear regression test probability value 0,018 < 0,050 means there is an effect of induction on changes in respiration. The results of bivariate analysis of each hemodynamic component include: Systolic Blood Pressure (P-value: 0.890; R2: 0.001); Diastolic Blood Pressure (P-value: 0.040; R2: 0.119); Mean Arterial Pressure (P-value: 0.149; R2: 0.060); Heart Rate (P-value: 0.283; R2: 0.034). The results of bivariat analysis of each respiration component include: Oxygen Saturation (P-value: 0.920; R2: 0.000); Minute Volume (P-value: 0.019; R2: 0.151); Spontaneous Breathing Time (P-value: 0.050; R2: 0.108). Conclusion: from this study it can be concluded from the simple linear regression test induction has no effect on hemodynamic changes, while the simple linear regression test induction affects respiration.